The Relationship Between Understanding the Concept of Light Polarization and the Level of Physical Creativity Among Sixth Scientific Grade Students - Abeer Abbas Hassan (Journal of Scientific and Human Dimensions, 2026)
The concept of light polarization is considered one of the abstract physical concepts that students often find difficult to comprehend, which may limit their creative abilities in the field of physics. The present study aims to explore the correlational relationship between sixth scientific grade students’ understanding of the concept of light polarization and their level of physical creativity, with a focus on identifying the nature of this relationship and its statistical significance.The study seeks to answer the main question: Is there a statistically significant positive correlation between students’ level of understanding of the concept of polarization (including its types linear, circular, and elliptical as well as methods of its production such as reflection, absorption, birefringence, and Malus’s Law) and their level of physical creativity represented by the dimensions of fluency, flexibility, and originality? The research adopted the descriptive correlational method. The tools were applied to a random sample of 150 sixth scientific grade students during the academic year 2025–2026. The instruments included a conceptual comprehension test consisting of 25 multiple-choice questions, whose validity and reliability were verified, and a physical creativity scale based on the Hu & Adey (2002) model to measure creativity, in addition to a questionnaire to collect demographic data. Statistical analysis using Pearson’s correlation coefficient revealed a moderate positive correlation (r = 0.966, p < 0.01), indicating that better conceptual understanding is associated with higher levels of creativity.The study concludes that enhancing conceptual understanding contributes to the development of scientific creativity. It recommends integrating interactive practical activities and creative experiments into physics teaching, as well as training teachers on strategies that promote creative thinking. It also suggests conducting future studies to explore mediating variables such as motivation and scientific anxiety